Effect of smartphone output power on the undetermined headache among high school students: Time-series study - W. Chogchitpaisan (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND | 2020. Background: The undetermined headache, which is not classified as a primary headache, might be a mobile phone associated headache (MPAH). Objective: To investigate the smartphone electromagnetic radiation related to undetermined headaches among high school students. Materials and Methods: One hundred forty-five high school students in the Chiang Mai Province completed a headache diary according to the International Classification of Headache Disorders version 3 beta criteria. It was scored according to the diagnosis algorithm. The smartphone output power (SOP) as measured and recorded by the smartphone application was saved every five minutes and transmitted by email. The completed data included 12,969 entries. The smartphone use, sleep quality, anxiety, and depression were also assessed. Data were analyzed using the Generalized Estimating Equation adjusted for demographic data, smartphone use, and sleep quality, and other. Results: Most students were female 74.7% with a mean age of 17.63±1.01 years (range 16 to 20). The one-year headache prevalence was 92.6% (95% CI 90.8 to 94.1) with undetermined headaches at 18.7% and 16.9% in the first and second phase, respectively. Characteristically, the prevalence of MPAH was higher in the nature of short duration pain, pulsing and tightening, indefinite form of pain, pain occurring in the morning, one side headache at occipital or frontal areas, and low pain severity (p<0.05). The results revealed the strongest effect of SOP at 1.80×10-5 to 1.99×10-5 mW range on the undetermined headaches with ORadj 2.32; 95% CI 1.23 to 4.34. Furthermore, the undetermined headaches also had the strongest association with handfree use and internet use (ORadj 1.92; 95% CI 1.11 to 3.29 and ORadj 2.33; 95% CI 1.71 to 3.19, respectively), age, and anxiety (ORadj 1.49; 95% CI 1.26 to 1.76 and ORadj 1.12; 95% CI 1.07 to 1.17, respectively). Conclusion: The undetermined headache associated with SOP, which was a MPAH. These results suggest that an older age for starting smartphone use and utilizing a hand-free device were recommended to prevent chronic headaches.